Perspektif Mahasiswa UNISKI Terhadap Fenomena Budaya Korea (Korean Wafe) dan Budaya Lokal (Local Wisdom) - Erlande, Rike; Sari, Novita (ASANKA : Journal of Social Science and Education, 2023)
ABSTRACTThe current rapid flow of globalization makes foreign culture enter through several media platforms without any filtering. Including Korean culture that enters and spreads among teenagers. Popular culture of the Korean wave or better known as the "Korean Wave/Hallyu" has its own characteristics in attracting devotees. Hallyu presents music, films, dance, television dramas, and culinary delights that suit the interests of the younger generation. In the past few years, Korean music or Korean pop and Korean dramas have been increasingly discussed. In addition, K-Pop has also become a trending topic on several social media such as Instagram and Twitter. Therefore, the entry of the Korean wave really needs to be discussed and reviewed for its development and its impact on Indonesian culture. The purpose of this research is to find out how the impact of the Korean Wave has on Indonesian culture. The method in this research is a qualitative method, with data collection techniques using questionnaires. The subjects in this study were students of Sriwijaya University. The results of the study stated that the Korean wave had a significant influence on students, not a few of these students were interested in finding out more about the culture in South Korea.  ABSTRAK Pesatnya arus globalisasi saat ini membuat budaya asing masuk melalui beberapa platform media tanpa adanya penyaringan. Termasuk budaya Korea yang masuk dan menyebar di kalangan remaja. Budaya populer gelombang Korea atau yang lebih dikenal dengan “Korean Wave/Hallyu” memiliki ciri khas tersendiri dalam menarik peminatnya. Hallyu menyajikan musik, film, Dance, drama televisi, hingga kuliner yang sesuai dengan minat generasi muda. Dalam kurun waktu beberapa tahun terakhir, musik Korea atau Korean pop dan drama Korea semakin marak diperbincangkan. Selain itu, K-Pop juga menjadi trending topic di beberapa media sosial seperti instagram dan twitter. Oleh karena itu masuknya Korean wave sangat perlu untuk dibahas dan ditinjau karena berdampak terhadap kebudayaan Indonesia. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana dampak dari Korean Wave terhadap kebudayaan Indonesia. Metode dalam penilitian ini adalah metode kuantitatif dengan teknik pengumpulan data menggunakan angket kuesioner. Subjek dalam penelitian ini adalah mahasiswa Universitas Sriwijaya. Hasil penelitian menyatakan bahwa Korean wave memiliki pengaruh yang signifikan pada mahasiswa, tidak sedikit dari mahasiswa tertarik untuk mencari tahu lebih dalam bagaimana kebudayaan di Korea Selatan.